2016
DOI: 10.1159/000452545
|View full text |Cite
|
Sign up to set email alerts
|

HOX Antisense lincRNA HOXA-AS2 Promotes Tumorigenesis of Hepatocellular Carcinoma

Abstract: Background: Recent studies reveal that long non-coding RNAs (LncRNAs) play critical roles in the proliferation and migration of human cancer. Previous report has shown that LncRNA HOXA-AS2 was involved in carcinoma processes. However, the expression and biological function of HOXA-AS2 in hepatocellular carcinoma (HCC) are poorly understood. Methods: Quantitative real-time PCR (qRT-PCR) was performed to detect the expression of HOXA-AS2 in HCC tissues and cell lines. The relation between lncRNA HOXA-AS2 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 25 publications
0
56
0
Order By: Relevance
“…Emerging evidence indicates key regulatory roles of lncRNAs in HCC [29,30]. However, evidence of lncRNAs with clinical prognostic value is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates key regulatory roles of lncRNAs in HCC [29,30]. However, evidence of lncRNAs with clinical prognostic value is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA HOXA cluster antisense RNA 2 (HOXA-AS2) was first reported to be an apoptosis suppressor in NB4 promyelocytic leukemia cells treated with all-trans retinoic acid [12]. Subsequent studies showed that HOXA-AS2 is aberrantly expressed in several human cancers and functions as an oncogene [13, 14]. However, little is known concerning its expression in glioma and its potential role in glioma malignancy and VM.…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of lncRNAs has been shown to contribute to initiation and progression in various human cancer types, including hepatocellular carcinoma, lung cancer, pancreatic cancer, osteosarcoma and colon cancer [13, 15, 16, 20]. Even though more and more lncRNAs have been reported to play crucial roles in osteosarcoma [15, 17, 21], the roles of lncRNAs in osteosarcoma are remain poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of C-myc staining in tissues was assessed by two independent professional pathologists who were blinded to patient clinical status and outcomes. C-myc expression scores were determined by the area of staining and the percentage of positive cells according to previous work [20]. …”
Section: Methodsmentioning
confidence: 99%